THE ASSESSMENT OF IMPACT ECOLOGICAL STABILITY OF TERRITORY ON THE ORGANIZATION OF RATIONAL LAND USE OF AGRICULTURAL ENTERPRISES - Ruslan TYKHENKO; Olga TYKHENKO; Ivan OPENKO; Oleksandr SHEVCHENKO; Nataliia BAVROVSKA; Oleksii ZHUK; Oleg TSVYAKH; Yanina STEPCHUK (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The ecological condition of agricultural land use is studied and the tendencies of significant changes of the ecological condition of lands in the process of transformation of land relations are revealed. Land valuation was carried out according to the degree of anthropogenic load. The coefficient of ecological stability of the territory, which is characterized by the level of intensive land use, is determined. Scenarios for the functioning of modern agroecosystems in agricultural land use have been developed. The main directions of ensuring an effective transition to an adaptive system of agriculture for the formation of efficient agricultural land use are outlined.